Does bilateral inferior turbinate reduction affect long‐term quality‐of‐life outcomes in patients undergoing endoscopic sinus surgery?. Issue 6 (31st January 2019) - Scangas, George A.; Bleier, Benjamin S.; Husain, Qasim; Holbrook, Eric H.; Gray, Stacey T.; Metson, Ralph
Abstract : Background: The objective of this study was to evaluate the impact of bilateral inferior turbinate reduction (BITR) on patient‐reported quality of life (QOL) following endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). Methods: This was a prospective cohort study. Patients with CRS, who were recruited from 10 different otolaryngologic practices between 2011 and 2014, completed the 22‐item Sino‐Nasal Outcome Test (SNOT‐22), Chronic Sinusitis Survey (CSS), and EuroQol 5 Dimension (EQ‐5D) survey at baseline, and at 12, 24, 36, and 48 months after ESS. A total of 113 patients who underwent ESS with BITR were compared to 788 patients who underwent ESS without BITR. Results: Significant demographic and comorbid differences between BITR and non‐BITR cohorts included age (41 vs 49 years, p < 0.0001), presence of asthma (19% vs 36%, p < 0.0001), prior sinus surgery (22% vs 53%, p < 0.0001), and concurrent septoplasty (80% vs 53%, p < 0.0001), respectively. On univariate analysis, patients who underwent ESS with or without BITR were found to have statistically significant improvement in disease‐specific (SNOT‐22 and CSS) and general (EQ‐5D) QOL scores at years 1 through 4 ( p < 0.05). On multivariate regression, however, the performance of BITR was not associated with any improvements in these outcome measures. Conclusion: Patients undergoing ESS achieve similar long‐term improvement in both disease‐specific and general QOL regardless of the performance of concurrent BITR.